2022
DOI: 10.1002/iju5.12523
|View full text |Cite
|
Sign up to set email alerts
|

Prostate cancer recurring as small‐cell carcinoma with a BRCA2 somatic mutation

Abstract: Introduction: Small-cell carcinoma of the prostate has a poor prognosis, and treatment options for the refractory disease are unclear. Case presentation: A 68-year-old man with prostate cancer was referred to our hospital. He was treated with combined androgen blockade (bicalutamide and degarelix acetate). The disease progressed to castration-resistant prostate cancer, but with additional treatment, prostate-specific antigen levels remained below 0.02 ng/mL. However, computed tomography revealed enlarged right… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 18 publications
0
0
0
Order By: Relevance
“…We speculate that although higher grade tumors are more likely to metastasize, that does not necessarily mean that they will spread to atypical locations. Inguinal LN metastases were seen throughout grade groups 1–5 in our study, as has been described in case reports ( 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 ) . In two cohorts of patients with predominantly high-grade group PCa who underwent dissection of pelvic LNs, metastasis in deep inguinal LNs was confirmed on pathology in only one (2.6%) and three (1.1%) of the 39 and 285 patients in each cohort, respectively ( 28 , 29 ) .…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…We speculate that although higher grade tumors are more likely to metastasize, that does not necessarily mean that they will spread to atypical locations. Inguinal LN metastases were seen throughout grade groups 1–5 in our study, as has been described in case reports ( 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 ) . In two cohorts of patients with predominantly high-grade group PCa who underwent dissection of pelvic LNs, metastasis in deep inguinal LNs was confirmed on pathology in only one (2.6%) and three (1.1%) of the 39 and 285 patients in each cohort, respectively ( 28 , 29 ) .…”
Section: Discussionsupporting
confidence: 89%
“…Recently, Schiller et al ( 4 ) investigated 799 LNs in 233 patients who underwent prostatespecific membrane antigen positron-emission tomography/computed tomography (PSMA PET/CT) and found that 10 inguinal LNs (1.3%) were suspicious (i.e., “PET-positive”), although there was again no verification by pathology. The remainder of the literature consists of a few case reports in which investigators raise hypotheses on potential pathways for the spread to inguinal LNs, such as altered lymphatic drainage after prostatectomy ( 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 ) . In clinical practice, questions regarding abnormal inguinal LNs raising concern for metastases are becoming increasingly common, especially with the growing popularity of molecular imaging (e.g., PSMA PET/CT).…”
Section: Introductionmentioning
confidence: 99%